Speech-in-Noise Tests and Supra-threshold Auditory Evoked Potentials as Metrics for Noise Damage and Clinical Trial Outcome Measures. Issue 8 (September 2016) - Le Prell, Colleen G.; Brungart, Douglas S.
Abstract : Objective: In humans, the accepted clinical standards for detecting hearing loss are the behavioral audiogram, based on the absolute detection threshold of pure-tones, and the threshold auditory brainstem response (ABR). The audiogram and the threshold ABR are reliable and sensitive measures of hearing thresholds in human listeners. However, recent results from noise-exposed animals demonstrate that noise exposure can cause substantial neurodegeneration in the peripheral auditory system without degrading pure-tone audiometric thresholds. It has been suggested that clinical measures of auditory performance conducted with stimuli presented above the detection threshold may be more sensitive than the behavioral audiogram in detecting early-stage noise-induced hearing loss in listeners with audiometric thresholds within normal limits. Methods: Supra-threshold speech-in-noise testing and supra-threshold ABR responses are reviewed here, given that they may be useful supplements to the behavioral audiogram for assessment of possible neurodegeneration in noise-exposed listeners. Conclusion: Supra-threshold tests may be useful for assessing the effects of noise on the human inner ear, and the effectiveness of interventions designed to prevent noise trauma. The current state of the science does not necessarily allow us to define a single set of best practice protocols. Nonetheless, we encourage investigators to incorporate these metrics into test batteries when feasible, with an effort to standardize procedures to the greatest extent possible as new reports emerge.